2015
DOI: 10.1177/0003489415619943
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Perception of Music in Children With Bimodal Fitting and Unilateral Cochlear Implant

Abstract: Bimodal fitting results in a better emotional perception of music compared to unilateral CI. Given the influence of music in neurological and linguistic development and social interactions, it is important to evaluate the possible benefits of bimodal fitting prescriptions for individuals with unilateral CIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
2
23
2
1
Order By: Relevance
“…Bimodal MCI performance was significantly better than CI-only performance, in agreement with previous studies that showed a bimodal advantage for music perception [ 5 , 10 , 11 , 13 , 19 , 46 , 47 ]. Previous studies have shown that adding low-frequency acoustic hearing in the contralateral ear can improve CI users' pitch perception ([ 46 , 48 , 49 ]).…”
Section: Discussionsupporting
confidence: 91%
“…Bimodal MCI performance was significantly better than CI-only performance, in agreement with previous studies that showed a bimodal advantage for music perception [ 5 , 10 , 11 , 13 , 19 , 46 , 47 ]. Previous studies have shown that adding low-frequency acoustic hearing in the contralateral ear can improve CI users' pitch perception ([ 46 , 48 , 49 ]).…”
Section: Discussionsupporting
confidence: 91%
“…8b), also suggests that bimodal users with poor residual hearing in their non-implanted ears may fare better with bilateral implants. Remaining residual low-frequency hearing has delayed implantation so that temporal fine structure for music and emotion perception, not available through CI use 63 , can be maintained 46,64,65 . However, children using bimodal devices with little residual hearing (PTA > 80 dB HL) do not perceive music or emotion better than their peers with bilateral implants 6668 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, bimodal hearing improves detection and understanding of speech in noise by providing access to sound from both sides of the head ( Arndt et al, 2015 , Arndt et al, 2017 , Ching et al, 2007 , Polonenko et al, 2015 , Thomas et al, 2017 ). Third, bimodal hearing preserves low-frequency acoustic hearing which works better than CI stimulation for pitch perception in music and speech ( Bartov and Most, 2014 , Giannantonio et al, 2015 , Polonenko et al, 2017 , Shirvani et al, 2016 ). Alternatively, when the non-implanted ear has poor residual hearing, findings from this study suggest that bimodal hearing cannot prevent preference for the implanted ear ( Fig.…”
Section: Discussionmentioning
confidence: 99%